2003 IEEE PES Transmission and Distribution Conference and Exposition (IEEE Cat. No.03CH37495)
DOI: 10.1109/tdc.2003.1335238
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive relaying for the protection of a wind farm interconnected with distribution networks

Abstract: This paper proposes the adaptive relaying of protective devices applied in the neighboring distribution feeders for reliable and efficient operations of a wind farm interconnected with distribution networks by dedicated lines. The wind farm connected with the electric power network is one of the great alternative energy sources; however, it would be also highly possible that the wind turbine generators are influenced by abnormal grid conditions such as disturbances occurring in the neighboring distribution fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Thus, the setting of wind farm collector network instantaneous protection should not only consider its short circuit current characteristics, but also require installing directional element if necessary [28,29]. An adaptive protection method based on short circuit current characteristics is presented in [30,31], which counters for different wind power output, short circuit current level and wind farm types. However, the presented researches have little consideration on LVRT control strategy for wind farm protection configuration and coordination.…”
Section: Research Status Of Wind Farm Protection Configurationmentioning
confidence: 99%
“…Thus, the setting of wind farm collector network instantaneous protection should not only consider its short circuit current characteristics, but also require installing directional element if necessary [28,29]. An adaptive protection method based on short circuit current characteristics is presented in [30,31], which counters for different wind power output, short circuit current level and wind farm types. However, the presented researches have little consideration on LVRT control strategy for wind farm protection configuration and coordination.…”
Section: Research Status Of Wind Farm Protection Configurationmentioning
confidence: 99%
“…Training function is ''scaled conjugate gradient back propagation''. 2 The diagram of 3rd neural network is shown in Fig. 9.…”
Section: Tablementioning
confidence: 99%
“…Obviously, the transmission system that connects such farms will be exposed to such a continuously changing environment. In most papers, topics related to protection of wind farms have discussed about over-current relay setting in distribution systems and adaptive schemes are proposed for distribution systems connected with wind generators [2,3]. The protection of transmission line connected to wind farms is discussed in [4].…”
Section: Introductionmentioning
confidence: 99%
“…They can successfully protect a wind turbine when an internal fault occurs. The proper delayed operation time of an over-current relay that is used in neighboring distribution feeders that are connected to a wind farm interconnected has been studied [2] by undertaking a case study. In that study, the simulation considered the various fault conditions and the power output of the wind farm demonstrated that the setting of the optimal operating time of the over-current relay could improve the operational reliability and stability of the wind farm.…”
Section: Introductionmentioning
confidence: 99%